Whiteness As Audition and Blackness As Performance: Status Protest from the Margin - John O. Calmore (Washington University Journal of Law & Policy, 2005)
This Essay seeks to make visible a white social identity that presents itself as abstract individualism while masking its support from systems of dominance. Against this hidden connection, blacks must not only represent our reality, but also advocate on its behalf to bring some balance to a form of dominant white voyeurism that places us in the ricocheting tension “between hypervisibility and oblivion.” Finally, I hope that my personal story provides an illustration of racialized experience that performs identity beyond this voyeurism and beyond what many whites cannot, or will not, see. In short, this Essay addresses racialized identity (blackness) as performance and whiteness as audition. Moreover, as a marginal man, I view my marginality as a positive position from which to launch a status protest.
Keywords: Critical race theory; Race preferences (Affirmative action)